2022
DOI: 10.3892/mco.2022.2594
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1 in different tumours and its clinical significance (Review)

Abstract: Mucin 1 (MUC1) was the first discovered transmembrane protein of the mucin family; it normally covers epithelial cells of the mucous membrane, providing lubrication and protection. However, aberrant expression of MUC1 is involved in cancer development, invasion and metastasis. It has been reported that MUC1 upregulation is highly associated with the progression of different epithelial cancer types, such as lung, liver, pancreatic and breast cancer. Therefore, MUC1 can be used as a specific marker and a target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Mucins are a family of high-molecular-weight glycoproteins. Among them, transmembrane protein mucin-1 (MUC1) is widely studied for its role in several kinds of cancers [ 1 ]. Usually, epithelial cells’ surfaces are covered in MUC1, which creates a dense mesh that protects cells from harsh external circumstances, forming a protective barrier across the mucosal surface [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mucins are a family of high-molecular-weight glycoproteins. Among them, transmembrane protein mucin-1 (MUC1) is widely studied for its role in several kinds of cancers [ 1 ]. Usually, epithelial cells’ surfaces are covered in MUC1, which creates a dense mesh that protects cells from harsh external circumstances, forming a protective barrier across the mucosal surface [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates high expression level of MUC1 in normal pancreas which is almost 50 times higher than the MUC13 expression. MUC1 is one of the oncogene in PanCa [25] and other cancers [7] , thus MUC1 holds the gold standard cancer biomarker status. Therefore, MUC1 was used as reference gene for the correlation analysis with MUC13.…”
Section: Discussionmentioning
confidence: 99%
“…Among all mucins, MUC1 is recognized as reference gene in gastro-intestinal cancers and its unusual upregulation is observed in more than 60% of PanCa incidents, which corelates with the poor prognosis of the patients. It has been observed that MUC1 upregulation is also linked to the progression of different types of cancer, such as ovarian, lung, liver, cholangiocarcinoma, gallbladder, thyroid, colorectal, pancreatic and breast cancer [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, transmembrane mucins are well-recognized for their role in cancer initiation, progression, metastasis, and immune evasion [12][13][14]16]. The abnormal expression of transmembrane mucins is one of the primary features of adenocarcinomas, which include colon, breast, pancreatic, lung, and ovarian cancer [20,36]. More than 90% of triple-negative breast cancers (TNBC) and 80% of pancreatic ductal adenocarcinoma (PDAC), both highly aggressive cancer types, present with the aberrantly expressed MUC1 [37,38].…”
Section: Muc1 Proteinmentioning
confidence: 99%